An examination in the role culture plays in the acceptance of e-learning at a global organization - Reed, Jaclyn, author; Kaiser, Leann, advisor; Gloeckner, Gene, committee member; Quick, Don, committee member; Switzer, Jamie, committee member (Colorado State University. Libraries, 2020)
One of the biggest challenges a global company faces when implementing e-learning is overcoming the cultural differences of its employees. Hofstede's Power Index Scale is a means to study how culture can impact an organization. In high-power-distance cultures, employees look to leaders as authorities and expect an uneven distribution of power. In low-power-distance cultures, employees see themselves as equal to and as powerful as the leaders. The population for this study was members of the Sales and Marketing and Human Resources departments at a global technology company with offices representing different national cultures and power distance levels. The purpose of this study was to determine how national culture, as measured by power distance, affects e-learning acceptance using the technology acceptance model as a framework. This nonexperimental, associational, comparative research study was a way to examine how a global company with employees representing different national cultures and varying levels of power distance accept e-learning based on perceived ease of use, perceived usefulness, behavioral intention, and actual usage of the Technology Acceptance Model (TAM). Answering the two research questions entailed determining whether there were correlations and/or differences between power distance, perceived usefulness, perceived ease of use, behavioral intention, and actual usage. This study used a survey to test the original TAM across multiple geographic locations. A Spearman's rho statistic and a one-way analysis of variance (ANOVA) were used to answer the research questions. The findings of the study support TAM as a reliable model but did not find a significant correlation between PDI scale and perceived usefulness, perceived ease of use, or behavioral intention but was weakly correlated to actual usage. The researcher had access only to Sales and Marketing and key members of Human Resources within a technology company. The participants represented were from developed counties with relatively strong e-learning market shares. Future researchers may want to explore the study in developing countries and may want to explore links between technology companies, self-efficacy, and their impact on e-learning acceptance.